The efficacy of autologous serum therapy in chronic spontaneous urticaria: A systematic literature review and meta-analysis - Suherman, Ahmad Ligar; Nopriyati; Pariyana (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2024)
Chronic spontaneous urticaria (CSU) is an autoimmune disease characterised by urtica lesions and/or angioedema accompanying an itching sensation, recurring for at least six weeks without any specific trigger. Autologous serum therapy (AST) is an adjuvant therapy for CSU that is resistant to H1 antihistamines. This therapy is an economical option in developing countries. There were a few studies discussing the role of AST in CSU. This systematic review and meta-analysis were conducted to evaluate the efficacy of AST based on urticaria activity scores (UAS or UAS7) and urticaria total severity scores (TSS) so that clinicians can consider them. Data were searched systematically in Cochrane, PubMed, Google Scholar, Willey, and EMBASE from 2000 to March 2023. Data analysis using Excel 2010 (Microsoft Corp) and MedCalc version 20.218. There were 14 studies: 4 randomised controlled trials (RCT), 9 prospective, and 1 cross-sectional. The average improvement in UAS and TSS scores at the end of therapy was 42.24% and 41.24%. Results of subgroup analysis of AST administration in the group autologous serum skin test (ASST) positive and ASST negative based on the end of therapy UAS score (p=0.18). Results of subgroup analysis of AST administration in the positive ASST and negative ASST groups based on the TSS score at the end of therapy (p=<0.001). Results of subgroup analysis of AST administration versus placebo based on TSS score (p=0.861). Based on subgroup analysis, autologous serum therapy improves TSS scores in CSU patients (ASST positive). However, AST is not significantly different from placebo.